Persepsi guru-guru terhadap stail kepimpinan pengetua yang mempengaruhi iklim sekolah :satu tinjauan di bahagian Kuching / Kota Samarahan, Sarawak - Pachappan, A/L Rajagopal. (1998)
This study is conducted to determine teacher's perception toward the principal's leadership style and its effects on the school climate. Subjects chosen for this study consisted of 245 confirmed teachers from 10 grade A secondary schools in the Kuching/Kota Samarahan Division of Sarawak. The questionnaire used for this is a modified version of the LBDQ (Leadership Behavior Discription Questionnaire) to test teachers' perception toward principal's leadership style and the C.F.K. Ltd. School Climate Profile which was used to test the school climate. Descriptive statistical analysis, t-Test One-Way Analysis of variance (ANOVA), correlation analysis and multiple regression stepwise analysis were employed in the study.